Determination of Antimicrobial Properties of Trifala, Java Plum, Cinnamon, Henna and Cumin - Zakaria Ahmed; Taslima Rahman; Sanchita Sarker (Innovations in Microbiology and Biotechnology Vol. 2, 2021)
In herbal medicine, crude plant extracts in the form of herbal extracts are used by the population for the treatment of diseases, including infectious diseases. Several hundred genera of plants are used as vital sources for potent and powerful drugs. The objective of present study were to determine the antimicrobial effect of some natural products of herbal and spice extracts; and compare the antimicrobial activity these aqueous and ethanolic extract test products with reference to MIC and MBC. The current study was carried out on five selected fresh samples from various conditions. Using the agar well and disc diffusion methods, the antimicrobial effects of Tripfala, Java plum, Cinnamon, Henna, and Cumin against both gram-positive and gram-negative bacteria were investigated. The zone of inhibition or antimicrobial activity of aqueous extracts of selected sample extracts was greater than that of ethanolic extracts. Among the five selected microbes, Klebsiella sp. had the lowest sensitivities to Tripfala and Java plum extracts, whereas these aqueous and ethanolic extracts had strong antimicrobial activity against four other microbes. The MIC values for all of the natural products ranged from 12.5-25.0 ug/ml, while the MBC values ranged from 25- 100.0ug/ml. During the four-month preservation of prepared discs of these natural plant products, no change in antimicrobial activity was observed. This research suggests that Tripfala and Java Plum have the potential to be used as a source of new broad-spectrum oral antibiotics.